Challenges of Social Trust in Disaster Management Focusing on COVID-19 in Iran: Recommendations for Gaining it Again - Hamid Reza khankeh; Mehrdad Farrokhi; Mohammadjavad Hosseinabadi-farahani; Mohammad Saatchi; Sina Ahmadi; Juliet Roudini; Amin Rahmatali Khazaee; Mariye Jenabi Ghods; Elham Sepahvand; Maryam Ranjbar; Taleb Badri; Mohammad Pourebrahimi (Health in Emergencies & Disasters Quarterly)
Background: Social trust in relief organizations is one of the prerequisites for community preparedness for disasters. This study aims to explore the challenges of social trust in disaster management in Iran with a focus on the COVID-19 pandemic, and provide recommendations for building social trust. Materials and Methods: This is a qualitative study using a conventional content analysis method. Participants were 27 lay people and managers of emergency and relief organizations in Tehran who were selected purposefully with maximum diversity. We used in-depth semi-structured interviews to explore their experiences and perceptions. Data analysis was performed using MAXQDA software, version 2018 and Graneheim and Lundman’s content analysis method. Results: In this study, two main themes emerged, “challenges to building social trust” and “recommendations for building social trust.” The challenges had four categories: Managerial issues, misunderstanding of the situation, lack of transparency, and lack of coordination. The recommendations had three categories: Management improvement, efficient risk communication, and experience-based interventions. Conclusion: Social trust during disasters in Iran can be improved by transparency in the performance and tasks of relief organizations, timely and accurate provision of information (risk communication), and emphasis on social participation and solving managerial issues.